2016
DOI: 10.1080/10810730.2016.1201174
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Is Associated With Health Behaviors and Social Factors Among Older Adults: Results from the LifeLines Cohort Study

Abstract: This study assesses the associations between health literacy and various health behaviors and social factors among older adults, and whether social factors moderate the other associations. Data from 3,241 participants in the LifeLines Cohort Study were analyzed (mean baseline age = 68.9 years). Data on health literacy, health behaviors (physical activity, fruit and vegetable consumption, smoking, breakfast consumption, alcohol consumption, and body mass index (BMI), and social factors (loneliness, social suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
106
6
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 50 publications
18
106
6
4
Order By: Relevance
“…17 Health literacy is known to be associated with age, physical activity and participating in social activities. 32,33 In line with these results from earlier studies, the oldest group in this study showed the lowest health literacy skills. On empowerment, no clinically relevant differences between groups were found.…”
Section: Discussionsupporting
confidence: 91%
“…17 Health literacy is known to be associated with age, physical activity and participating in social activities. 32,33 In line with these results from earlier studies, the oldest group in this study showed the lowest health literacy skills. On empowerment, no clinically relevant differences between groups were found.…”
Section: Discussionsupporting
confidence: 91%
“…Parker, Baker, Williams, and Nurss (1995) found high correlations among measures of general literacy skills (WRAT-R), literacy in medicine (REALM), and functional health literacy (TOFHLA). 1 Both low literacy and low health literacy have been reliably associated with poor health outcomes such as poorer health knowledge, poor overall health status, measures of morbidity, and use of health resources (DeWalt, Berkman, Sheridan, Lohr, & Pignone, 2004;Geboers, Reijneveld, Jansen, & De Winter, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As reported in literature, an adequate level of health literacy is needed to make an appropriate health decision. 7 Public health agencies believed there was a relationship between health literacy and hygiene in children. 8 In a meta-analysis, previous findings suggest that only limited knowledge existed about the effects of hand hygiene education on multiple illness outcomes.…”
mentioning
confidence: 99%